Kualitas Susu Cair Pasca Pasteurisasi Setelah Penambahan Sirup Oligofruktosa Umbi Talas Kimpul (Xanthosoma sagittifolium Schott.) - Mukarlina, Mistia Ningsih, Tri Rima Setyawati, (Jurnal Protobiont, 2014)
One alternative of fresh milk preservation is by adding sugar that derived from the hydrolysis process of blue taro tuber. The aim of this study was to examine the quality of fresh milk after the addition of oligofructose syrup. The study was carried out from April to June in 2013. Based on the ANOVA test, it was known that the concentration of oligofructose syrup influenced the increase of proximately test, total number of bacteria, and reduction time of milk. The protein content of milk increased to 0.25% after being added by oligofructose syrup with 20% concentration, and then it became 3.95 %. The lactose content increased to 2.05% after being added by oligofructose syrup with 40% concentration, and then it become 6%. The highest increment of milk acidity occurred over milk by adding 40% of oligofructose syrup. Furthermore, 40% milk fat and oligofructose syrup decreased to 2.40%, which it became 2%. Total number of milk bacteria decreased to 23x103 CFU/ml after being added by 40% oligofructose syrup, but then it become 26x103 CFU/ml. In this study, no indication of coliform was found in all milk samples. Best time of reducing bacteria occured over milk added 40% syrup is 634 minutes.